A Stiff Person Syndrome Misdiagnosed as a Psychiatric Illness: A Case Report - Souissi, Mohamed-Anis; Bellakhal, Syrine; Gharbi, Emna; Abdelkefi, Istabrak; Douggui, Mohamed-Hedi (Current Rheumatology Reviews, 2020)
Background: Stiff Person Syndrome (SPS) is a rare autoimmune neurological disorder which is often misdiagnosed. We report here a case of SPS with a long diagnosis delay. Case: A 36-year-old man presented with an 11-year history of progressive stiffness and painful spasms of his both legs, with recent worsening of his condition over the last year resulting in a considerable difficulty of standing up and walking. As the patient developed phobic symptoms, he was considered as having a psychiatric illness and treated with antianxiety and antidepressant drugs. As no real improvement was observed, the patient was referred to internal medicine. Neurological examination showed paraspinal, abdominal and lower limbs muscle contraction with lumbar rigidity. These symptoms were associated to adrenergic symptoms: profuse sweating, tachycardia and high bloodpressure. Initial routine investigations revealed high blood glucose level. Polygraphic electromyographic (EMG) evaluation from paraspinal and leg muscles showed continuous motor unit activity in agonist and antagonist muscle. Electroencephalography and brain magnetic resonance imaging were normal. Immunologic tests according to radio immune assay technique revealed high level of serum anti-glutamic acid decarboxylase (anti-GAD65) antibodies. Diagnosis of autoimmune SPS was retained based on clinical, electrophysiological, and immunological findings. Pregabalin at the dose of 150 mg, three times a day was prescribed with satisfying response. Conclusion: SPS is supported by an autoimmune pathogenesis and anti-GAD antibodies seems to be very helpful when SPS is clinically suspected. Treatment of SPS is a challenge, given the scarcity of the syndrome and the absence of established recommendations.
Keywords: phobic disorder